2021
DOI: 10.2320/matertrans.z-m2020858
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Oxynitriding of Ti–6Al–4V Alloy by Induction Heating in Air

Abstract: In this study, a rapid oxynitriding technique based on induction-heating was developed for the titanium alloy Ti6Al4V, and its effects on surface characteristics of the alloy were investigated. The surface microstructures of the alloy were characterized by employing a scanning electron microscope, electron back-scatter diffraction, X-ray diffraction and nano-indentation tests. Induction-heating in air for 60 s caused the formation of a hardened layer on the Ti6Al4V alloy surface, which can be attributed to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…11) Moreover, the authors also revealed that IH in air can form a hardened layer at the surface of Ti6Al4V alloy due to reaction with the elements contained in air. 12) These previous studies revealed that IH can accelerate the diffusion of elements surrounding the heated titanium.…”
Section: Introductionmentioning
confidence: 95%
“…11) Moreover, the authors also revealed that IH in air can form a hardened layer at the surface of Ti6Al4V alloy due to reaction with the elements contained in air. 12) These previous studies revealed that IH can accelerate the diffusion of elements surrounding the heated titanium.…”
Section: Introductionmentioning
confidence: 95%
“…Dry etching requires expensive devices and ancillary equipment, such as gas removal devices, which increase cost and limit the size of substrates. In our previous studies, we used fine particle bombarding (FPB) (Tamura et al 2021 ; Morita et al 2020 ; Ohue et al 2008 ; Morita et al 2013 ) to achieve microscale roughness. In FPB, a microscale rough surface is formed by bombarding fine particles, such as ceramics, onto a metal surface.…”
Section: Introductionmentioning
confidence: 99%